(-)-Phenserine Ameliorates Contusion Volume, Neuroinflammation, and Behavioral Impairments Induced by Traumatic Brain Injury in Mice. Issue 9 (September 2019) - Hsueh, Shih-Chang; Lecca, Daniela; Greig, Nigel H.; Wang, Jia-Yi; Selman, Warren; Hoffer, Barry J.; Miller, Jonathan P.; Chiang, Yung-Hsiao
Traumatic brain injury (TBI), a major cause of mortality and morbidity, affects 10 million people worldwide, with limited treatment options. We have previously shown that (-)-phenserine (Phen), an acetylcholinesterase inhibitor originally designed and tested in clinical phase III trials for Alzheimer's disease, can reduce neurodegeneration after TBI and reduce cognitive impairments induced by mild TBI. In this study, we used a mouse model of moderate to severe TBI by controlled cortical impact to assess the effects of Phen on post-trauma histochemical and behavioral changes. Animals were treated with Phen (2.5 mg/kg, IP, BID) for 5 days started on the day of injury and the effects were evaluated by behavioral and histological examinations at 1 and 2 weeks after injury. Phen significantly attenuated TBI-induced contusion volume, enlargement of the lateral ventricle, and behavioral impairments in motor asymmetry, sensorimotor functions, motor coordination, and balance functions. The morphology of microglia was shifted to an active from a resting form after TBI, and Phen dramatically reduced the ratio of activated to resting microglia, suggesting that Phen also mitigates neuroinflammation after TBI. While Phen has potent anti-acetylcholinesterase activity, its (+) isomer Posiphen shares many neuroprotective properties but is almost completely devoid of anti-acetylcholinesterase activity. We evaluated Posiphen at a similar dose to Phen and found similar mitigation in lateral ventricular size increase, motor asymmetry, motor coordination, and balance function, suggesting the improvement of these histological and behavioral tests by Phen treatment occur via pathways other than anti-acetylcholinesterase inhibition. However, the reduction of lesion size and improvement of sensorimotor function by Posiphen were much smaller than with equivalent doses of Phen. Taken together, these results show that post-injury treatment with Phen over 5 days significantly ameliorates severity of TBI. These data suggest a potential development of this compound for clinical use in TBI therapy.